Unmanned Aerial Vehicle (UAV) for heritage tree detection / Khalilah Hassan, Siti Norlizaiha Harun and Siti Rasidah Md Sakip - Hassan, Khalilah; Harun, Siti Norlizaiha; Md Sakip, Siti Rasidah (2018)
This paper explores the potentials of Unmanned Aerial Vehicle (UAV) as a satisfying alternative tool to detect potential heritage trees by assessing the tree characteristic - the crown spread. Tree crown spread is an essential variable in tree assessment but is typically costly and time-consuming to measure in the field survey using conventional techniques. The study was carried out by a case study at Taman Perbandaran Tengku Anis, Kota Bharu. The first phase presents the procedure of capturing and processing UAV data to create and digital surface models in GIS environment. This information was used to detect the potential of heritage trees of the average crown spread estimated by the cross method. In the second phase, the researcher validated the accuracy of the methods by comparing the results with ground measurements. The results showed higher agreement between field survey and the UAV data for the crown spread, which were in the range 1.0- 1.5 meters. Overall, the results accuracy was acceptable and showed that the method was feasible for tree crown measurement.Thus,as an alternative way of detecting the potential of heritage tree withindirect measures of tree characteristics. Within this study, the researchers save precious time and money that can be put in to restore before the ground survey was conducted. Reliable information is available within hours. The UAV has proven to be a useful tool for urban forestry providing a cost-effective and reliable system to obtain remotely sensed data. This information offers better method of potential heritage tree detection which is the basis for protection, care, and management of heritage tree for the future.